A study on efficacy of oral administration of colostrum fortified lactoferrin in the weight gain of low birth weight infants - Jayaseelan, Raghul; Sivaprakasam, Chidambaranathan; Palanisamy, Logesvar (International Journal of Contemporary Pediatrics, 2019)
Background: Low birth weight babies is the result of being small for gestational age (i.e. under 10th percentile of the reference population) and preterm (i.e. before 37 weeks of gestation. Preterm infants have higher protein, calorie requirement, which cannot be met with unfortified breast milk feeds. Methods: This study was conducted prospectively in the Department of Pediatrics, Rajah Muthiah Medical College and Hospital, Chidambaram from October 2016 to April 2018. 20 low birth weight babies were selected by randomization technique and they were administered with 2 grams of oral colostrum fortified lactoferrin daily for 4 weeks. The rate of weight gain, length gain and head circumference gain were assessed prospectively for a period of 4 weeks. They were analysed statistically by ANOVA and tabulated. Babies weighing less than 2.5 kg and on exclusive breast feeding, were included. Babies more than 2.5kg and less than 1kg, at risk for neonatal sepsis, congenital heart disease, necrotizing enterocolitis were excluded from the study. Results: In the present study, 20 low birth weight babies were included. 11 maternal risk factors were identified. Out of which anemia stands as a single risk factor. The rate of weight gain in oral colostrum fortified lactoferrin, is 320 grams with P value of 0.703 which is not statistically significant. The rate of length gain is 3.3cm, p value is 0.093 which is statistically insignificant. The rate of head circumference gain in oral colostrum fortified lactoferrin is 2.8cm, with the p-value of 0.001 which is statistically significant. Conclusions: The rate of weight and length gain was normal, but the rate of head circumference gain is significantly increased in oral colostrum fortified lactoferrin supplementation.